Differences in Mental Health Status Among Asian Americans During the COVID-19 Pandemic: Findings from the Health, Ethnicity, and Pandemic Study (Mary Ann Liebert, 2022)
Purpose: This study aims to explore the differences in mental health status among Asian Americans during the COVID-19 pandemic. Methods: Data from the 2020 Health, Ethnicity, and Pandemic (HEAP) Study were used to explore the psychological distress of 2672 adults, using the Standard Kessler Psychological Distress Scale. Results: We observed that among Asian American subgroups, South Asian Americans had significantly higher odds of experiencing psychological distress than non-Hispanic White Americans (odds ratio?=?1.82, 95% confidence interval?=?1.00?3.31), after controlling for covariates. Conclusion: The study identified differences in mental health status among Asian American subgroups. We recommend the implementation of culturally appropriate interventions to help Asian Americans cope with mental health challenges.